21ST Century Language Teachers With Freeware for Language Learning - John Pahamzah; Rahman Hakim (Bandar Lampung University (UBL), 2013)
This article discusses about categories of freeware that become considerable tools and skills for 21st century language teachers. It investigatesthe course of language laboratory management subject the writers introduced during the lecturesin the last semester. The writer assumes that the 21st century language teachers are expected to have competence in preparing and managing both face-to-face and online learning. The writers assume that by using freeware teachers can support the antipiracy campaign, and it is the cheapest and safest way anyone can afford, instead of using unauthorized or pirated software. There are four categories of freeware that will be discussed: 1) audio editing tools to record and edit audio files for teaching listening skills; 2). language laboratory management software; 3) software for creating the e-learning materials such as hot potatoes and moodle; and 4) video editing and subtitling tools.